Study of erysipelas vaccine: Immunogenicity of three culture fractions of E. rhusiopathiae serotype 2 local isolate on swine - Siti Chotiah (Indonesian Center for Animal Research and Development (ICARD), 2008)
Erysipelothrix rhusiopathiae as the causal agent of erysipelas was isolated from swine in Indonesia. The aims of this study were to develop a local isolate vaccine for erysipelas and determine its immunogenicity in swine. Three types of fractionated culture of local isolate E. rhusiopathiae serotype 2 consisting of whole culture (WCu), whole cell (WCe) and culture filtrate (CF) were made into an oil adjuvant at a final bacteria concentration about 1010 colony forming unit (CFU). Four groups of swine (12 swines/group) were vaccinated intra muscularly with WCu, WCe and CF containing 2 ml per dose respectively, and K as a control group without vaccination. The vaccine was injected twice with three weeks interval. All groups were challenged with local isolates of E. rhusiopathiae; serotype 1 (heterologous) and serotype 2 (homologous) at five weeks after second vaccination except CF group was challenged at twelve weeks after the second vaccination by 107.5 CFU. The specific antibody responses were monitored every two weeks by ELISA technique, and protective responses were determined by clinical signs of erythema urticaria or mortality during the observation for 14 days. The results showed that the antibody responses of WCu, WCe, and CF groups against extract antigen were not different. The protective responses of groups WCu, WCe, CF, and K against challenged local isolate of homologous serotype and heterologous were 83.3, 83.3, 91.7 and 0% respectively, with average value of optical density 0.492, 0.454, 0.529 and 0.3450 respectively, at the time of challenge. Cross protection occurred on all culture fractions tested. In conclusion, the three culture fractions of local isolate of E. rhusiopathiae serotype 2 containing protective antigen and could be used for vaccine candidate in Indonesia. Key Words: Erysipelothrix rhusiopathiae, Local Isolate, Immunogenicity, Swine, Vaccine